Implementasi Peraturan Tanah Absentee Dalam Hubungannya Dengan Kepemilikan Tanah Pertanian Di Kabupaten Temanggung - Nanda Putri Ariska; Rahayu Subekti; Purwono Sungkowo Raharjo (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This legal research aims to investigate how absentee land regulations are implemented in relation to agricultural land ownership in Temanggung Regency. The main objective is, first, to understand how absentee land regulations are implemented in relation to agricultural land ownership in Temanggung Regency. Second, to identify the factors that cause absentee ownership and control of land in Temanggung Regency. This research is a type of empirical juridical legal research that is descriptive in nature. This research method uses primary data obtained through direct interviews with the Temanggung Land Office and people who own absentee land. The research results show that absentee ownership and control of land still occurs in Temanggung Regency due to less than optimal implementation of the authority of the Temanggung Land Office. This condition occurs because there are buying and selling transactions outside official mechanisms and a lack of clear records by the Temanggung Regency Land Office regarding land inheritance. Several factors that cause the emergence of absentee land control and ownership in Temanggung Regency include legal aspects, law enforcement, community participation, infrastructure and culture.